Phytotoxicity of Profenofos 50% EC (curacron 50 EC) to Vigna radiata,L. seedlings: II. Studies on Biochemical Parameters - Mishra, I.P.; Sabat, G.; mohanty, Bijaya Kumar (International Journal of Applied Sciences and Biotechnology, 2015)
Profenofos 50% EC (curacron 50 EC) is a hazardous pesticide commonly used in agriculture is also an important contaminant of environment.Its presence in biological system has gained importance due to bioaccumulation in food chain. The phyto-toxic effect of profenofos wasassessed based on the biochemical parameters (Shoot and Root) of seedlings (Amino acids, Protein, Sugar, DNA and RNA) of the test species,Vigna radiata,L. The concentrations of pesticide chosen were based on EC50 and are in the range of 0.02, 0.05, 0.08, 0.1 and 0.2 % ofprofenofos. The biochemical parameters like Amino acid, Sugar, DNA and RNA were significantly reduced with increase in pesticideconcentration whereas Protein concentration increased with the profenophos treatment. The increase in amino acid was more pronounced inShoot of the seedlings than root.DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12063    Int J Appl Sci Biotechnol, Vol. 3(1): 101-105